ULTRASONOGRAPHIC CHARACTERIZATION OF OVARIAN FOLLICULAR DYNAMICS IN UMBLACHERY COWS - V. Umanath; S. Satheshkumar; S. Raja; A.S. Selvaramesh; N. Narmatha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Ultrasonographic characterization of ovarian follicular dynamics was carried out in two subsequent oestrous cycles in Umblachery cows (n =10) from the day of observed oestrum (Day 0) to next oestrum. Two subsequent oestrous cycles were studied in all the animals. Out of 20 cycles studied, seven (35.00%), twelve (60.00%) and one (5.00%) cycle(s) had two, three and four waves respectively. The day at which the Wave-1 dominant follicle (DF) attained the maximum diameter varied widely from Day 5 to Day 11. It was also found that the day of Wave-2 emergence varied widely from Day 7 to Day 13 among the individual animals. The average diameters of anovulatory wave DFs ranged from 9.07 to 9.86 and that of ovulatory wave DFs averaged from 9.20 to 9.67 mm. The mean inter-oestrus intervals were significantly (P < 0.01) longer in cycles with three-follicular waves (22.17 ± 0.27 days) than two-follicular waves (19.43 ± 0.28 days). Even though follicular wave patterns were comparable with other crossbred and B.indicus cattle, smaller size of the DF and wide variation in the days to attaining maximum diameter and emergence of Wave-2 were found to be characteristic features of Umblachery cows.